Effect of partial root-zone drying, storage temperature and days to ripening on post-harvest quality of 'hass' avocado fruit - Mukovhanama, Khangwelo Jessica (My University, 2019)
The South African Avocado Industry is continuously expanding with ‘Hass’ cultivar occupying the largest land and therefore, the most exported cultivar. Expansion of the industry implies an increased demand for irrigation water. However, South Africa is a water scarce country characterised by low and erratic rainfall, where fruit production relies heavily on irrigation. The agricultural sector is under an obligation to reduce water use due to the increasing demand for water by other economic sectors. Therefore, it must find efficient water use techniques to save water and ensure water availability for other economic sectors. Partial root-zone drying (PRD) is an irrigation technique which may lead to 50% reduction in water use, half of the root system is kept wet while the other half is left dry to a predetermined level of soil water depletion, the dry and the moist sides are alternated at regular intervals. During storage and transportation of fresh produce, low temperature is a post-harvest tool used to maintain quality, especially when fruit are destined for long distant export markets. This study investigated the effect of PRD and low temperature storage on post-harvest quality parameters of ‘Hass’ avocado fruit. The experiment was laid as a factorial arranged in randomised complete block design (RCBD). The treatment factors for chilling injury, electrolyte leakage and vascular browning were 2 x irrigation regimes (Full Irrigation (FI) vs. PRD) and 2 x storage temperatures (2.0 and 5.5°C). However, treatment factors for fruit weight loss, respiration rate, fruit firmness, ripening percentage and fruit skin colour were 2 x irrigation regimes (Full Irrigation (FI) vs. PRD), 2 x storage temperatures (2.0 and 5.5°C) and 4 ripening days (0, 2, 4 and 6 days). Mature ‘Hass’ avocado fruit were harvested from PRD and fully irrigated trees and thereafter fruit of each treatment were stored at 2.0 and 5.5°C for 28 days. Each treatment consisted of 6 replicates, with an exception of electrolyte leakage, whereby the experiment was replicated 4 times. After 28 days’ storage at 2.0 and 5.5°C, fruit were ripened at 21°C. The effect of PRD and low temperature storage was determined by evaluating the following physico-chemical fruit parameters during ripening: external chilling injury, electrolyte leakage, fruit weight loss, respiration rate, firmness, fruit skin colour and vascular browning. During ripening, ‘Hass’ avocado fruit stored at 2.0°C showed significantly higher incidences of external chilling injury symptoms compared with xiii 5.5°C, irrespective of irrigation treatment. Furthermore, an interaction between irrigation treatment and low storage temperature had a significant (P<0.05) effect on cell membrane electrolyte leakage. All evaluated fruit showed similar weight loss, irrespective of irrigation and storage treatment. Irrigation, storage temperature and ripening days did not have effect on respiration during ripening. Fruit reached the respiratory climacteric peak on the same day (day 2). Furthermore, there was no significant interaction effect (P˃0.05) on fruit firmness. However, PRD treated fruit showed slightly low firmness when compared with control fruit. ‘Hass’ avocado fruit harvested from PRD and fully irrigated trees and stored at 5.5°C ripened quicker compared to fruit stored at 2.0°C. There was no significant interaction effect (P˃0.05) on fruit skin lightness (L), chroma (C), hue angle (h°) and fruit eye colour due to irrigation and cold storage treatment. In general, fruit showed skin colour change from emerald green to approximately 75% coloured. Furthermore, irrigation and storage temperature did not have effect on vascular browning, however, there incidence was high on fruit stored at 2.0°C when compared with 5.5°C. The results of this study indicated that ‘Hass’ avocado fruit stored at 2.0°C was negatively affected by low temperature storage and this cold storage temperature is not recommended. PRD reduced water use during irrigation, however, its effect on post-harvest quality of ‘Hass’ avocado fruit subjected to 5.5°C must be further investigated before recommended for export markets.
Thesis (M. Sc. (Horticulture)) -- University of Limpopo, 2019
Keywords: Chilling injury; Physico-chemical parameters; Respiration rate; Vascular browning; Weight loss; Avocado; Avocado industry